Thyroid status of males with acute infectious pulmonary destruction - S. N. Ermashkevich; V. I. Petukhov; M. V. Kuntsevich; V. V. Yangolenko; L. V. Tikhonova (Сибирский научный медицинский журнал, 2020)
The aim of the study was to investigate the indicators of the thyroid status in males with acute infectious pulmonary destruction (AIPD), depending on the disease form and the presence of complications. Material and methods. The serum levels of total triiodothyronine (T3), total thyroxine (T4) and thyroid-stimulating hormone (TSH) were measured by radioimmunoassay in 80 males with AIPD and 30 healthy males volunteers. Results. T3 serum level is decreased in males with AIPD and is not depended on the disease form and complications. T3 serum level reduction is occurred due to decrease of peripheral conversion of thyroid hormones. If AIPD is complicated by sepsis, then T4 production is reduced. T4 serum level correlates with the presence of sepsis in males with AIPD (rS = –0.49; p = 0.000003). The sepsis probability threshold in males with AIPD for value T4 is ≤95.5 nmol/L with a sensitivity of 100 % and a specificity of 62.5 %. Thyroid function remains normal in 25 % (95 % CI: 16–34) of males with AIPD, in other cases it is represented by: primary hypothyroidism – in 11 % (95 % CI: 4–18), nonthyroidal illness syndrome (NTIS) type I – in 44 % (95 % CI: 33–55), NTIS type II – in 11 % (95 % CI: 4–18), NTIS type V – in 9 % (95 % CI: 3–15). NTIS type II is associated with the highest mortality rate (pFisher = 0.0015). T4 serum levels correlate with mortality in males with AIPD (rS = –0.37; p = 0.00082). The mortality probability threshold in males with AIPD for value T4 is ≤70.1 nmol/L with a sensitivity of 68.7 % and a specificity of 78.1 %. The obtained data indicates the advisability of monitoring and analysis of the thyroid status indicators in males with AIPD for the diagnosis of sepsis and prognosis of the disease outcome.